The Enigmatic Canal-Associated Neurons Regulate Caenorhabditis elegans Larval Development Through a cAMP Signaling Pathway. Issue 4 (1st December 2019) - Chien, Jason; Wolf, Fred W; Grosche, Sarah; Yosef, Nebeyu; Garriga, Gian; Mörck, Catarina
Abstract: Caenorhabditis elegans larval development requires the function of the two Canal-Associated Neurons (CANs): killing the CANs by laser microsurgery or disrupting their development by mutating the gene ceh-10 results in early larval arrest. How these cells promote larval development, however, remains a mystery. In screens for mutations that bypass CAN function, we identified the gene kin-29, which encodes a member of the Salt-Inducible Kinase (SIK) family and a component of a conserved pathway that regulates various C. elegans phenotypes. Like kin-29 loss, gain-of-function mutations in genes that may act upstream of kin-29 or growth in cyclic-AMP analogs bypassed ceh-10 larval arrest, suggesting that a conserved adenylyl cyclase/PKA pathway inhibits KIN-29 to promote larval development, and that loss of CAN function results in dysregulation of KIN-29 and larval arrest. The adenylyl cyclase ACY-2 mediates CAN-dependent larval development: acy-2 mutant larvae arrested development with a similar phenotype to ceh-10 mutants, and the arrest phenotype was suppressed by mutations in kin-29 . ACY-2 is expressed predominantly in the CANs, and we provide evidence that the acy-2 functions in the CANs to promote larval development. By contrast, cell-specific expression experiments suggest that kin-29 acts in both the hypodermis and neurons, but not in the CANs. Based on our findings, we propose two models for how ACY-2 activity in the CANs regulates KIN-29 in target cells.